Characterization and therapy monitoring of head and neck carcinomas using diffusion-imaging-based intravoxel incoherent motion parameters: preliminary results - Hauser, Thomas; Essig, Marco; Jensen, Alexandra; Gerigk, Lars; Laun, Frederik B.; Münter, Marc; Simon, Dirk; Stieltjes, Bram (Neuroradiology, 2013)
Using the intravoxel incoherent motion (IVIM) model, diffusion-related coefficient (D) and perfusion-related parameter (f) can be measured. Here, we used IVIM imaging to characterize squamous cell carcinomas of head and neck (HNSCC) and evaluated its application in follow-up after nonsurgical organ preserving therapy.